Pengaruh Hasil Belajar Mata Kuliah Arsip Digital dan Kuliah Kerja Lapangan (KKL) Terhadap Persepsi Profesi Arsiparis pada Mahasiswa Pendidikan Administrasi Perkantoran Universitas Negeri Jakarta - Imel Ahmarita Meliana; Marsofiyati Marsofiyati (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2025)
The purpose of this study is to understand how far the influence of Learning Outcomes and Fieldwork Lectures on the Perception of the Archivist Profession in Office Administration Education students class of 2022, State University of Jakarta. This study uses a quantitative approach through a survey conducted by distributing questionnaires. This study uses the application of JASP statistics for accurate and fast data processing. From the partial test carried out, it was found that the two variables, namely Learning Outcomes and Field Work Lectures, each had a significant influence on the Perception of the Archivist Profession. In addition, from the simultaneous test, it was found that the two variables, namely Learning Outcomes and Field Work Lectures, simultaneously had a significant influence on the Perception of the Archivist Profession. These results are also evidenced by the determination coefficient test which shows that the variables of Learning Outcomes and Field Work Lectures contribute 56.7% to the Perception of the Archivist Profession.